Faktor-Faktor yang Mempengaruhi Produktivitas Mesin Forging Press dengan Metode Failure Model and Effectiveness Analytics (FMEA) - Ahmad Fikri Assidik; Kardiman Kardiman (Peneliti.net, 2022)
PT. Fujita Indonesia is a company engaged in manufacturing which in the production process uses the help of machines. One of the machines used is the Forging Press machine. From previous research, it is known that the productivity of the Forging Press machine still has not reached the required productivity standard value. Therefore, the purpose of this openelitian is to find out the causal factors that affect productivity at PT. Fujita Indonesia. Data is secondary data or based on pt. Fujita Indonesia in January-April 2021. The method used is Failur Mode Effectiveness Analysis (FMEA). The results of the study found the causal factors that affect the low productivity of the Forging Press machine, namely an abnormal BKA alarm and a damaged machine, then PT. Fujita needs to pay more attention and take care of these two things in order to increase productivity.